The digital dentist: robotics in dental practice - Kumal, Monika; Ray, Neha; Sah, Pinky; Gupta, Jayantika; Kumar, Abhishek (International Journal of Research in Medical Sciences, 2025)
The integration of robotics into dentistry marks a significant technological advancement, leading to transformation in traditional dental practices. This review explores the varied applications of robotics in dentistry, including surgical procedures, implantology, orthodontics, prosthodontics, and endodontics, highlighting their ability to improve accuracy, reduce human error, and streamline workflow. Robotic systems, such as surgical assistants, CAD/CAM-enabled devices, and AI-powered diagnostic tools, are revolutionizing patient care by providing minimally invasive options and superior treatment outcomes. However, these innovations are not without challenges. High initial costs, a steep learning curve, and concerns about the loss of human touch in dental care hinder widespread adoption. Patient skepticism and fear, coupled with ethical considerations about replacing traditional methods with automated systems, also pose barriers. Additionally, technical limitations, such as extended preparation times and the need for robust maintenance, underscore the complexity of integrating robotics into clinical practice. The current trend emphasizes the growing collaboration between robotics, artificial intelligence, and digital dentistry, aiming to create more accessible and reliable solutions. With advancements in autonomous systems and AI, robotics holds the potential to bridge gaps in accessibility, provide care in remote areas, and redefine the scope of dental practice. This review highlights the need for further research, interdisciplinary collaboration, and public education to address existing limitations and foster acceptance of robotics in dentistry, ultimately paving the way for a future of more precise and patient-centered dental care.